(untitled) (CAHIERS MAGELLANES-NS, 2024)
Аbstract. This article analyzed the scientific research conducted on the design of comfortable clothing for people with limited mobility. Statistics of people with limited mobility were studied. The distribution of people with limited mobility according to the type of disease, age and disability group was considered. The relevance of production of clothes that provide comfort during exploitation to the part of the population with limited physical capabilities was highlighted. Factors of clothing that have a negative effect on the psycho-physiological condition of people with limited mobility using wheelchairs have been determined. The goals and tasks for the development of flexible clothing for people with limited mobility were defined and the object of research was selected. Interviews and questionnaires were conducted among women in "Inclusive Society" and "Mehribonlik" society in Tashkent city and Tashkent region in order to identify, analyze, and conduct sociological research on the advantages and disadvantages of existing clothes of people with limited mobility. 50 respondents aged 17 to 35 took part in it. According to the results of the conducted sociological survey, it was found that 50% of the women who took part in the survey belonged to the first and second groups of disabilities.